Investigating the formation of acid mine drainage of toledo pyrite concentrate using column cells - Aguila, Diosa Marie M.; Mendoza, Herman D. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Acid mine drainage (AMD) is an inevitable problem in the mining industry, from its beginning until the end of mine operations. The main culprit is the presence of sulfides, especially pyrite, which is associated with many valuable minerals including copper. AMD is known for having high metal load, excessive acidity and precipitates, which have adverse effects in the environment. Studying AMD formation is important because it will pave way in developing methods to control the composition of mine waters and planning the rehabilitation method for a mine area. The objective of this study is to investigate the formation of AMD of Toledo pyrite using two-stage column cell experiments. The first stage, where mechanisms of AMD formation and the effects of particle size, amount of pyrite and volume of leachate on pH drop of solution were studied, was done using twelve column cells. The second stage was done using a larger column cell for validation and to study the role of ferrous to ferric ratio in change of solution pH. The results of the first experiment revealed that aside from time, particle size has the most significant effect in pH, which resulted to decrease in pH from starting pH of 5.6 to 30th day pH of 2.8 It was also observed that the sudden drop of pH during the starting hours was due to the following: a) cracks formed from the beneficiation, which increased the surface area of the pyrite available for reaction; and, b) the formation of Fe(OH)3 precipitates which increased the formation of hydrogen ions. Moreover, the ladderized behavior of pH drop thereafter was due to the buffering effect of the redissolution of ferric hydroxides and it subsequent precipitation onto the pyrite surface that lowered the surface area available for oxidation. The results of the second experiment validated the ladderized behavior of pH. It was also observed that particle size distribution and pyrite surface were affected by the change in pH. Scanning electron microscopy was used to study the surface of pyrite, and precipitates were seen to be more abundant in the surtace of pyrite taken from pH 2.4 solution than in pH 3.1 solution, validating the assumptions made in the first experiment. On the other hand, based on the per cent passing graph done to investigate the effect of particle size distribution, results showed that as solution pH decrease, particle size consequently decreased. Moreover, ferrous to ferric ratio of the solution generally decreased as AMD was continuously generated.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Acid mine drainage; Pyrites